2015
DOI: 10.1007/s11547-015-0514-4
|View full text |Cite
|
Sign up to set email alerts
|

3D versus 2D contrast-enhanced sonography in the evaluation of therapeutic response of hepatocellular carcinoma after locoregional therapies: preliminary findings

Abstract: Objective: To investigate diagnostic performance of 3D contrast-enhanced ultrasound (CEUS) compared with 2D CEUS in the assessment of therapeutic response of hepatocellular carcinoma (HCC) treated with locoregional therapies (LRT). Materials and methods: Twenty-three consecutive patients (13 men and 10 women; mean age 65.5 years) with 23 HCCs (size range 1.2–7.2 cm; mean size 2.9 ± 1.4 cm) treated by means of radiofrequency ablation (RFA n = 9), transarterial chemoembolization (TACE n = 8), combined RFA and TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In one recent study 2D and 3D CEUS 1 month (30±2 days) after treatment were compared using MRI and CT as standard of reference. No statistically significant difference between 2D and 3D CEUS in depicting either complete response or residual tumor was found [29]. It should be noted that these are preliminary results and in order to show the theoretical superiority of 3 D CEUS new data is mandatory needed.…”
Section: New Ceus Techniques To Evaluate the Efficacy Of Tacementioning
confidence: 81%
“…In one recent study 2D and 3D CEUS 1 month (30±2 days) after treatment were compared using MRI and CT as standard of reference. No statistically significant difference between 2D and 3D CEUS in depicting either complete response or residual tumor was found [29]. It should be noted that these are preliminary results and in order to show the theoretical superiority of 3 D CEUS new data is mandatory needed.…”
Section: New Ceus Techniques To Evaluate the Efficacy Of Tacementioning
confidence: 81%
“…More recently, three-dimensional CEUS technique (3D CEUS) has been reported to improve the study of tumour vascularity, thus allowing the response evaluation of HCC treatments in the three orthogonal planes. Nevertheless, it has been suggested that the spatial resolution of the current 3D probes may be limited as 3D CEUS provided similar diagnostic performance compared to conventional CEUS in the assessment of therapeutic response of HCC treated with ablative treatments [59] .…”
Section: Resultsmentioning
confidence: 99%
“…18 The complete ablation rate of the CEUS group was significantly higher than that of the CECT group, which might benefit from immediate postoperative examination, assessment of ablation effects, as well as the rapid and repeated ablations. 19 There was a congestion and edema region appearing around the tissues undergoing RFA and it is hard to distinguish the congestion zone from tumor residuals through the CECT. The RFA effects could only be assessed 1 month after the congestion zone had disappeared.…”
Section: Discussionmentioning
confidence: 99%